Complejo turístico de salud y belleza a base de insumos naturales propios de la región oriente de Cundinamarca: Plan parcial de Bio-Conservación Choachí (2017)
A chain is designed to concentrate the tourist activities of health, beauty and relaxation, the route consists of four projects in different stops, each with a different theme but with the same purpose of health tourism. The project was located in stop three of this tour, which is a tourism complex in health and beauty, which is focused on physical therapies and aesthetic care, offering treatments (facials, body, alternative-medicine and spa Relaxation) based on natural products created in the research laboratories of potato, uchuva and tomato. As a medicinal support to the hot springs that treat rheumatic diseases.